Dose-dependent impact of enrofloxacin on broiler chicken gut resistome is mitigated by synbiotic application - Temmerman, Robin; Ghanbari, Mahdi; Antonissen, Gunther; Schatzmayr, Gerd; Duchateau, Luc; Haesebrouck, Freddy; Garmyn, An; Devreese, Mathias (Frontiers in Microbiology, 2022)
Fluoroquinolone agents are considered critical for human medicine by the World Health Organization (WHO). However, they are often used for the treatment of avian colibacillosis in poultry production, creating considerable concern regarding the potential spread of fluoroquinolone resistance genes from commensals to pathogens. Therefore, there is a need to understand the impact of fluoroquinolone application on the reservoir of antibiotic resistance genes in poultry gut and devise means to circumvent potential resistome expansion. Building upon a recent dose optimization effort, we used shotgun metagenomics to investigate the time-course change in the cecal microbiome and resistome of broiler chickens receiving an optimized dosage (12.5 mg/kg body weight(bw)/day), with or without synbiotic supplementation ((PoultryStar®, BIOMIN GmbH), and a high dosage of enrofloxacin (50 mg/kg bw/day). Compared to the high dose treatment, the low (optimized) dose of enrofloxacin caused the most significant perturbations in the cecal microbiota and resistome of the broiler chickens, demonstrated by a lower cecal microbiota diversity while substantially increasing the antibiotic resistance genes (ARGs) resistome diversity. Withdrawal of antibiotics resulted in a pronounced reduction in ARG diversity. Chickens receiving the synbiotic treatment had the lowest diversity and number of enriched ARGs, suggesting an alleviating impact on the burden of the gut resistome. Some Proteobacteria were significantly increased in the cecal metagenome of chickens receiving enrofloxacin and showed a positive association with increased ARG burden. Differential abundance analysis revealed a significant increase in the abundance of ARGs encoding resistance to macrolides-lincosamides-streptogramins (MLS), aminoglycosides, and tetracyclines over the period of enrofloxacin application, with the optimized dosage application resulting in a two-fold higher number of affected ARG compared to high dosage application. Our results provide novel insights into the dose-dependent effects of clinically important enrofloxacin application in shaping the broiler gut resistome, which was mitigated by a synbiotic application. The contribution to ameliorating the adverse effects of antimicrobial agents, that is, lowering the spread of antimicrobial resistance genes, on the poultry and potentially other livestock gastrointestinal microbiomes and resistomes merits further study